Pollination ecology of shea (Vitellaria paradoxa C.F. Gaertn.) in the Guinea Savanna Zone of Ghana - Nasare, Latif Iddrisu (University of Cape Coast, 2022)
Vitellaria paradoxa (shea) is an economic tree endemic to Sub-Saharan Africa. Shea fruit contributes to food security, while the edible fat from shea kernel is used industrially in cosmetic, pharmaceutical and confectionary products. However, optimum fruit yield is limited by inadequate pollination services. This study investigated floral phenology and explored managed bee (Apis mellifera) for enhanced pollination in shea parklands of six sites in three regions (Upper West, Upper East and North East) from August 2020 to December 2021. The study specifically sought to establish the relationship between climatic conditions and floral phenology, and the effect of apiary on shea flower visitors and fruit yield at four distances (100, 500, 1000 and 4000m) from the apiary. Alternative floral resources visited by shea pollinators (bees) were also surveyed monthly for one year. Shea flowering was significantly associated with soil moisture and temperature but the onset of flowering and morphometric traits of floral parts varied significantly between regions. Tree proximity to apiary had a positive effect on fruit set but not fruit weight and size. Presence of apiary did not have any effect on diversity and flower visitation frequency of other bees. Similarly, weather conditions had a minimal effect on flower visitor composition. Alternative forage survey identified 32 woody plants, 75% of which were visited by shea primary pollinators. The study concluded that beekeeping in shea parklands had some positive effects on pollination and fruit set. However, further studies are required to determine the optimal hive density per acreage of shea parkland and the long-term effects of beekeeping on other florivorous insects.
xiv, 207p,; ill.
Keywords: Sub-Saharan Africa; Shea; climatic; pollination